Analisis Tindak Tutur Tersangka Disabilitas dalam Dugaan Kasus Pelecehan Seksual Agus Iwas di NTB : Sebuah Kajian Pragmatik - Salma Fauziah Raudatul Jannah; Kundharu Saddhono (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to explore speech acts in the statement of AI with disabilities who is a suspect in a sexual harassment case. The object of research refers to voice recordings that become digital forensic evidence and are uploaded by YouTube tvOneNews as news of the development of the case. The research method used is descriptive qualitative with data collection techniques of observing information related to the development of the case which is then analyzed. The data collection technique uses a digital media observation system. The results and discussion found that there are locution, illocution, and perlocution speech acts. The locution is in the form of AI's statement to the speech partner (potential victim). The illocution contained 3 assertive verbs, 2 directive verbs, 2 commissive verbs, 1 expressive verb, and 2 rogative verbs. The perlocution contained is convincing so as to cause the effect of speech partners to feel sad. Emotional manipulation is present through the diction used by AI to influence its victims. In this context, it is also evident that anyone can commit acts of sexual harassment as long as they have mastery of language and regulation of thinking to manipulate victims.